Pengaruh Jenis Kelamin Janin dengan Derajat Asma pada Ibu Hamil Trimester II dan III - Lia Octaviana; Ivon Diah Wittiarika; Arief Bakhtiar (JURNAL ILKES : Jurnal Ilmu Kesehatan, 2023)
Background: Asthma is still a health problem in the community in almost all countries including Indonesia. The results of a preliminary study conducted by researchers at UNAIR Hospital Surabaya on January 26, 2022, the number of pregnant women with a history of asthma who visited Obstetric Poly, Pulmonary poly, maternity room in January - March 2021 as many as 10 mothers, and there are pregnant women with a history of controlled and uncontrolled asthma with different degrees of asthma and gestational age. Based on these results, it was also obtained that sex of the baby was born with more ratios in female infant as much as 3.79% of the total pregnant women with a history of asthma. The purpose of this study was to analyze the relationship of fetal sex influence with the degree of asthma of pregnant women in the second and third trimesters. Methods: A type of observational analytical research with a Retrospective approach. The total population of pregnant women is 264 with a sample of pregnant women with a history of asthma as many as 31 mothers. Result: Processing research results was carried out which was then carried out statistical tests with the Fisher Exact test obtained a p value of ˂ 0.05. The value is less than the value of α = 1%. Thus, there is a relationship between the Mother's Asthma Degree and the Sex of the Baby they are giving birth to. Furthermore, the Contingency Coefficient test obtained C value of 0.557, so it can be concluded that there is a relationship between the influence of fetal sex and the degree of maternal asthma that has a moderate or sufficient relationship. Conclusion: Based on the results of the analysis using the Fisher exact test, it is known that the sex of the fetus has an influence on the degree of asthma of pregnant women. Most female fetal sex affects the degree of severe asthma, while male fetus tend to have intermittent asthma degrees.